Extramuscular Recording of Spontaneous EMG Activity and Transcranial Electrical Elicited Motor Potentials in Horses: Characteristics of Different Subcutaneous and Surface Electrode Types and Practical Guidelines - Journée, Sanne Lotte; Journée, Henricus Louis; Reed, Stephen Michael; Berends, Hanneke Irene; de Bruijn, Cornelis Marinus; Delesalle, Cathérine John Ghislaine (Frontiers in Neuroscience, 2020)
Adhesive surface electrodes are worthwhile to explore in detail as alternative to subcutaneous needle electrodes to assess myogenic evoked potentials (MEP) in human and horses. Extramuscular characteristics of both electrode types and different brands are compared in simultaneous recordings by also considering electrode impedances and background noise under not mechanically secured (not taped) and taped conditions. Methods. In 5 ataxic and one non ataxic horses transcranial electrical MEPs, myographic activity and noise were simultaneously recorded from subcutaneous needle (3 brands) together with pre-gelled surface electrodes (5 brands) on 4 extremities. In 3 horses, the impedances of 4 adjacent placed surface electrode pairs of different brands were measured and compared. The similarity between needle and surface EMGs was assessed by cross-correlation functions, pairwise comparison of motor latency times (MLT) and amplitudes. The influence of electrode noise and impedance on the signal quality was assessed by a failure rate (FR) function. Geometric means and impedance ranges under not taped and taped conditions were derived for each brand. Results. High coherencies between EMGs of needle-surface pairs degraded to 0.7 at moderate and disappeared at strong noise. MLTs showed sub-millisecond simultaneous differences while sequential variations were several milliseconds. Subcutaneous MEP amplitudes were somewhat lower than epidermal. The impedances of subcutaneous needle electrodes were below 900  and FR=0. For 4 brands the FR for surface electrodes was between 0-80% and declined to below 25% after taping. A remaining brand (27G DSN2260 Medtronic) revealed impedances over 100 kand FR=100% under not taped and taped conditions. Conclusion. Subcutaneous needle and surface electrodes yield highly coherent EMGs and TES-MEP signals. When taped and allowing sufficient settling time, adhesive surface electrode signals may approach the signal quality of subcutaneous needle electrodes, but still depend on unpredictable conditions of the skin. The study provides a new valuable practical guidance for selection of extramuscular EMG electrodes. This study on horses shares common principles for the choice of adhesive surface or sc needle electrodes in human applications such as in intraoperative neurophysiological monitoring of motor functions of the brain and spinal cord.